Morphological development of Malay ESL learners: The processability perspective - Wan Hamdan, Wan Nur Adila (2020)
To date, studies using the Processability Theory (henceforth PT) in analysing Malay ESL learners’ English language are limited. The current study aims at investigating the development of past tense ‘–ed’ and present continuous ‘–ing’ on two Malaysian ESL learners. Additionally, the study also aims to see the applicability of PT on Malay ESL learners’ developmental path. For 10 weeks, Communicative Approach was employed to elicit the data from the learners and their output were recorded. The output was then analysed using PT hierarchy. Findings indicated that the students showed progress over the weeks and the developments for past tense ‘–ed’ and present continuous ‘–ing’ followed the stages hypothesised by PT. The study might contribute to the field of PT analysis as well as Malay ESL learners’ ESL development.